1977
DOI: 10.1590/1809-43921977073355
|View full text |Cite
|
Sign up to set email alerts
|

Precipitable water and water vapor flux between Belém and Manaus()

Abstract: The water vapor flux and precipitable water was computated over the natural Amazon forest in the stretch between Belem and Manaus for 1972. The atmospheric branch of hidrological cycle teory was applied and the most significant conclusions on an annual basis are: Atlantic Ocean water vapor contributes 52% to the regional precipitation and is significant the role played by local evapotranspiration in the precipitation in the area; there were signs of the phenomenon of water vapor recycling nearly throughout the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
8

Year Published

1985
1985
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 0 publications
2
15
0
8
Order By: Relevance
“…Molion (1976) and Lettau et al (1979), by means of climatonomic analysis, have concluded that 50% of the present precipitation in the Amazonian rainforest comes from water recycled by the vegetation itself and the other 50% from the Atlantic ocean. This fact was further corroborated by other methodologies (Marques, 1976;Marques et al, 1977;Salati, 1987). Later, Nobre et al (1988) concluded that 58% of rainfall came from local evapotranspiration.…”
Section: Uncertainties In Simulation Models For South Americasupporting
confidence: 77%
“…Molion (1976) and Lettau et al (1979), by means of climatonomic analysis, have concluded that 50% of the present precipitation in the Amazonian rainforest comes from water recycled by the vegetation itself and the other 50% from the Atlantic ocean. This fact was further corroborated by other methodologies (Marques, 1976;Marques et al, 1977;Salati, 1987). Later, Nobre et al (1988) concluded that 58% of rainfall came from local evapotranspiration.…”
Section: Uncertainties In Simulation Models For South Americasupporting
confidence: 77%
“…For example, Russell and Miller (1990) shows a high evapotranspiration ratio, since the parameterization of evapotranspiration or that of groundwater storage is not adequate. In Russell and Miller (1990), the evapotranspiration from tropical forests was estimated by the bulk formula and was also overestimated, being almost as same as the annual potential evapotranspiration calculated by the Thornthwaite method (Marques et al, 1977). The GCM's spatial resolution (4**5*) might be one of the reasons for the overestimation of evapotranspiration.…”
Section: Comparison With Previous Studiesmentioning
confidence: 86%
“…In addition to the estimation of the annual evapotranspiration using the water balance method of the basin, Villa nova et al (1976) and Marques et al (1977) calculated the annual potential evapotranspiration from fairly wide area, if not the entire basin. In these studies, the annual evapotranspiration estimated by the water balance method was smaller than the annual potential evapotranspiration and their results are in contraciction with those of the small experimental area near Manaus.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Disturbance of the vegetation cover not only changes the surface albedo, but also can affect the surface-atmosphere energy exchange, by altering the relative proportions of sensible to latent heat (the Bowen ratio), largely through changes in evapotranspiration. Up to 50% of the rainfall on Amazonian tropical forests may be recycled through evapotranspiration (Marques et al, 1977;Salati and Vose, 1984). Thus large-scale forest clearance could significantly affect evapotranspiration and precipitation.…”
Section: Climatic Implications Of Anthropogenic Vegetation Modificationmentioning
confidence: 99%